Analysis of the Factors Affecting Violent Crime Rates in the US - Dr. Abhijeet Bhattacharya (International Journal of Engineering and Management Research, 2020)
The goal of this study is to analyze the factors affecting violent crime rates in the US. It is hypothesized that an increase in the gun ownership rate tends to increase violent crimes in the US. It is hypothesized that urban areas in the US tend to have more violent crimes than rural areas. An OLS regression model is formulated using cross-sectional data set across 50 states and the District of Columbia for the year 2019. The endogenous variable is the violent crime rates per 100,000 inhabitants across 50 states and the District of Columbia. The independent variables used in the OLS regression model are population density per square mile, unemployment rate, percentage of the population living in poverty, and gun ownership rate. The four exogenous variables that are found to be statistically significant are gun ownership, unemployment rate, population density per square mile, and percentage of population living in property. An attempt is also made to formulate strategies that would help in reducing violent crime rates in the US.